PENERAPAN APLIKASI SIAPIK DALAM MENYUSUN LAPORAN KEUANGAN PADA UMKM CATERING DAPUR MAMANUM BREBES - I Sabila, Nur Fadilatul Nisa; Noerman Syah, Asrofi Langgeng; Aryanto (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
The lack of awareness of MSME actors in recording transactions and preparing financial reports, on the grounds that they waste time and consider it difficult, Bank Indonesia and IAI collaborated to launch the SIAPIK application. This study aims to determine the application of the SIAPIK application in recording transactions and preparing financial reports at Mamanum Kitchen. Data collection methods are carried out through observation, interviews, literature study and documentation. The data analysis technique used in this research is data reduction, data presentation, and conclusion drawing. The results of this study can be useful and provide information for MSME actors so that it can be used as a reference for implementing the SIAPIK application so that it can assist in the process of recording and reporting finances so that companies can find out the profit or loss generated. Based on the results of the study, it can be concluded that the application of the SIAPIK application at Dapur Mamanum can provide benefits to improve the quality of human resources, as a planning tool, and as an evaluation material. Keywords: Financial Statements, Transactions, MSMEs, SIAPIK